(untitled) (Quaderni di Gargnano, 2018)
The essay proposes a partial review of the biography of Giovanni Della Casa’s young years. By reorganising and re-examining the letters Della Casa wrote between 1530 and 1537 to his principal correspondents, Ludovico Beccadelli, Carlo Gualteruzzi and Cosimo Gheri, Manzocchi introduces fresh biographical detail. In particular, the cross-analysis of the material allows the author to date and trace Della Casa’s movements with greater precision and shed new light on his cultural activities and literary endeavours.